Maturity of Personality, Purpose of Life and Value System in Nuns During a Midlife Crisis - Vavreková, Erika; Wodawski, Marek (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
This article aims to deepen our understanding of the midlife crisis of nuns (a study group) and women living alone (a control group). We present the results of an empirical study conducted on a group of 100 women aged 35–45. This study aimed to discover whether convent life, along with its spiritual-religious formation, may have a positive influence on the ability of women to deal with a midlife crisis and aid the development of their mature personalities by strengthening their sense of purpose and shaping their value systems. The issue tackled by this article can be contained in the following question: Is religious formation central to convent life able to support a person in a midlife crisis in gaining a higher degree of personal maturity? We may gain an answer to this by considering whether nuns engaged in such religious formation compared to women living alone would exhibit any differences in personal maturity and a sense of life’s purpose and value system.